Estimated glomerular filtration rates are higher when creatinine‐based equations are compared with a cystatin C‐based equation in coronavirus disease 2019. Issue 2 (26th November 2022) - Larsson, Anders O.; Hultström, Michael; Frithiof, Robert; Lipcsey, Miklos; Nyman, Ulf; Eriksson, Mats B.
Abstract: Objectives: Estimations of glomerular filtration rate (eGFR) are based on analyses of creatinine and cystatin C, respectively. Coronavirus disease 2019 (COVID‐19) patients in the intensive care unit (ICU) often have acute kidney injury (AKI) and are at increased risk of drug‐induced kidney injury. The aim of this study was to compare creatinine‐based eGFR equations to cystatin C‐based eGFR in ICU patients with COVID‐19. Methods: After informed consent, we included 370 adult ICU patients with COVID‐19. Creatinine and cystatin C were analyzed at admission to the ICU as part of the routine care. Creatinine‐based eGFR (ml/min) was calculated using the following equations, developed in chronological order; the Cockcroft–Gault (C‐G), Modified Diet in Renal Disease (MDRD)1999, MDRD 2006, Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI), and Lund–Malmö revised (LMR) equations, which were compared with eGFR calculated using the cystatin C‐based Caucasian Asian Pediatric Adult (CAPA) equation. Results: The median eGFR when determined by C‐G was 99 ml/min and interquartile range (IQR: 67 ml/min). Corresponding estimations for MDRD1999 were 90 ml/min (IQR: 54); MDRD2006: 85 ml/min (IQR: 51); CKD‐EPI: 91 ml/min (IQR: 47); and for LMR 83 ml/min (IQR: 41). eGFR was calculated using cystatin C and the CAPA equation value was 70 ml/min (IQR: 38). All differences between creatinine‐based eGFR versus cystatin C‐based eGFR were significant ( p < .00001). Conclusions: Estimation of GFR based on various analyses of creatinine are higher when compared with a cystatin C‐based equation. The C‐G equation had the worst performance and should not be used in combination with modern creatinine analysis methods for determination of drug dosage in COVID‐19 patients.